COVID-19 onset reduced the sex ratio at birth in South Africa - Masukume, Gwinyai; Ryan, Margaret; Masukume, Rumbidzai; Zammit, Dorota; Grech, Victor; Mapanga, Witness (PeerJ, 2022)
Background The sex ratio at birth (defined as male/(male+female) live births) is anticipated to approximate 0.510 with a slight male excess. This ratio has been observed to decrease transiently around 3–5 months following sudden unexpected stressful events. We hypothesised that stress engendered by the onset of the COVID-19 pandemic may have caused such a decrease in South Africa 3–5 months after March 2020 since in this month, South Africa reported its first COVID-19 case, death and nationwide lockdown restrictions were instituted. Methods We used publicly available, recorded monthly live birth data from Statistics South Africa. The most recent month for which data was available publicly was December 2020. We analysed live births for a 100-month period from September 2012 to December 2020, taking seasonality into account. Chi-squared tests were applied. Results Over this 100-month period, there were 8,151,364 live births. The lowest recorded monthly sex ratio at birth of 0.499 was in June 2020, 3 months after March 2020. This June was the only month during this period where the sex ratio inverted i.e., fewer male live births occurred. The predicted June 2020 ratio was 0.504. The observed June 2020 decrease was statistically significant p = 0.045. Conclusions The sex ratio at birth decreased and inverted in South Africa in June 2020, for the first time, during the most recent 100-month period. This decline occurred 3 months after the March 2020 onset of COVID-19 in South Africa. As June 2020 is within the critical window when population stressors are known to impact the sex ratio at birth, these findings suggest that the onset of the COVID-19 pandemic engendered population stress with notable effects on pregnancy and public health in South Africa. These findings have implications for future pandemic preparedness and social policy.
Keywords: Sex ratio at birth; COVID-19; South Africa; Population stressor